Influence of nozzle geometry on primary and large-scale instabilities in coaxial injectors. (10th August 2020) - Kumar, Abhijeet; Sahu, Srikrishna
Highlights: Influence of nozzle exit geometry on jet instabilities in coaxial injectors is studied. Nozzles with different fluid area ratio ( AR ) and lip-thickness-ratio ( LTR ) are considered. Kelvin-Helmholtz and flapping instabilities are characterized using high speed imaging. The fluctuations of jet breakup length are considerably affected by nozzle geometry. Strouhal number of jet instability are found to bear strong correlations with AR and LTR . Injector exit geometry plays an important role in triggering the interfacial disturbances. Abstract: Detailed knowledge on liquid jet instabilities is important to improve the performance of coaxial injectors, which find wide range of industrial applications. The present paper aims to investigate the influence of nozzle exit geometry on jet instabilities during the unsteady primary jet breakup process in liquid-centered coaxial injectors. Time resolved images of the liquid jet were processed to characterize Kelvin–Helmholtz instability close to the nozzle exit and flapping instability near the jet breakup location for three different nozzles with different liquid-to-gas cross-sectional area ratio ( AR ) and lip thickness to diameter ratio ( LTR ) of the central tube. The results showed considerable effect of AR and LTR on both primary and large scale instabilities as well as jet breakup length and morphology. It is found that the injector exit geometry plays a crucial role in triggering the interfacial disturbances as it conditions the liquid and air flow prior to their interaction.